Power : Its myths and mores in American art 1961-1991 - Chave, Anna C.; Day, Holliday T.; Marcus, George E.; Roberts, Catsou; Wallis, Brian; Akron Art Museum, Akron; Virginia Museum of Fine Arts, Richmond (Indianapolis : Indianapolis Museum of Art, 1991)
Acconci, Vito ; Adams, Dennis ; Artschwager, Richard ; Bickerton, Ashley ; Burden, Chris ; Burson, Nancy ; Clegg & Guttmann ; Halley, Peter ; Holzer, Jenny ; Judd, Donald ; Koons, Jeff ; Kruger, Barbara ; Laub, Stephen ; Lawler, Louise ; Lichtenstein, Roy ; Longo, Robert ; de Maria, Walter ; Morris, Robert ; Nauman, Bruce ; Prince, Richard ; Serra, Richard ; Sherman, Cindy ; Simpson, Lorna ; Steinbach, Haim ; Stella, Frank ; Tasset, Tony ; Warhol, Andy ; Wodiczko, Krzysztof
geboorteplaats en -datum per kunstenaar
Engels
Power : Its myths and mores in American art 1961-1991, Indianapolis Museum of Art, Indianapolis, September 5 - November 3, 1991 ; Akron Art Museum, Akron, January 18 - March 21, 1992 ; Virginia Museum of Fine Arts, Richmond, Virginia, May 11 - July 12, 1992
boek
Keywords: Amerika